The use of mixed sources for the sociological diagnosis of municipalities - De-Gracia-Soriano, Pablo; Jareño-Ruiz, Diana; Jiménez-Delgado, María; Monllor-Jiménez, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this contribution is to detail the process to carry out a study on the population of a municipality that allows the elaboration of a sociological diagnosis. To do this, demographic, economic, social and public participation variables will be identified. The process allows to obtain the minimum and necessary information for the development of the first phase of a project focused on the planning of public policies: the sociological diagnosis phase. The study of these structural elements allows obtaining detailed results of the population and preparing the fundamental theses on the needs and social problems that arise.